Understanding Student Purpose Types and Student Perceptions of the Influences Shaping Them. Issue 2 (3rd April 2017) - Robinson, Jessica; Glanzer, Perry
Abstract: The authors undertook a qualitative study involving a national sample of 75 college students to discover what factors influenced their purpose development. They found that students generally fit into four different purpose types: the Purposeless, the Self-Achievers, the Relationalists, and the Transcendents. Moreover, these different purpose types were motivated toward deeper purpose development by different influences, interactions with mentors, and ideological beliefs. These findings may prove helpful for student life professionals and faculty alike who are creating a common language to discuss purpose across their campuses.